Application of manual aspiration thrombectomy in the treatment of deep vein thrombosis in cancer patients: Descriptive retrospective cohort study. - Eu Hyun Kim (Public Library of Science (PLoS), 2021)
Objectives To determine the outcomes and feasibility of endovascular treatment, mainly based on manual aspiration thrombectomy (MAT) with adjunctive percutaneous balloon angioplasty with or without stent deployment, for treatment of symptomatic ilio-femoral deep vein thrombosis (IFDVT) in cancer patients. Materials and methods In this retrospective cohort study, 135 consecutive patients (56 men; mean age, 63 years; 149 limbs) with acute (n = 113; 83.7%) and subacute to chronic (n = 22; 16.3%) symptomatic IFDVT underwent MAT-based endovascular treatment. Among them, adjunctive balloon angioplasty and stent placement was performed in 94 patients. Technical and clinical success regarding stage and cause of DVT was assessed. Results Technical success (complete thrombus removal without residual thrombus or stenosis) was achieved in 89.6%, and subjective symptom improvement was stated by 71.5% of treated patients. The primary patency rates were 88.1%, 81.6%, 76.0%, 74.1% and 69.1% at 1, 3, 6, 12, and 30 months, respectively. Recurrent IFDVT occurred in 19.3% (26/135) of patients, 0.79 cases per patients-years of follow up. According to the analysis by causes of IFDVT, recurrence rate was 19.3% (11/57), 21.2% (12/57), and 14.3% (3/21) in unknown, compression/invasion of the vein by cancerous mass, and May-Thurner syndrome groups, respectively (p = 0.798). No procedure-related complication developed. Conclusions Endovascular treatment based on MAT is a feasible treatment option with favorable outcomes and minimal risk of complication in cancer patients with symptomatic IFDVT.